A complex scalp resurfacing utilizing Integra® as temporary dressing in aplasia cutis congenita - Pauline Yap; Nurul Syazana Mohamad Shah; Arman Zaharil Mat Saad; Wan Azman Wan Sulaimana; Siti Fatimah Noor Mat Johar (Eco-Vector, 2021)
BACKGROUND: Aplasia cutis congenita is a rare newborn malformation characterized by focal absence of skin. It possesses difficulty in reconstruction surgery for neurosurgeons and plastic surgeons. We report a challenging case of aplasia cutis congenita who received treatment in our center. CLINICAL CASE: A 2-year-old boy, presented to Plastic and Reconstructive Surgery, Hospital USM, with bilateral vertex defect with encephalocele who received a series of surgical interventions since 1 month old. Unfortunately, he returned after 2 years with a chronic nonhealing scalp wound associated with dura defect and cerebral spinal fluid leakage. The wound was debrided and the swab culture result showed no organism growth. Part of the wound bed with dura defect was repaired using a small piece of transplanted fascia lata and Integra® was applied. DISCUSSION: There is scarcity in the medical literature on the reconstructive technique of aplasia cutis congenita. In the case we described here, we successfully managed the wound with multiple application of dermal substitute (Integra®) dressing with negative pressure wound therapy and split-thickness skin graft. CONCLUSIONS: Management of aplasia cutis congenita with skull defect remains a controversy. Its management varies depends on its pattern and underlying condition. We successfully develop a new simple method in treating scalp accutilizing Integra®.